Diabetes mellitus in the Russian Federation: dynamics of epidemiological indicators according to the Federal Register of Diabetes Mellitus for the period 2010–2022 - I. I. Dedov; M. V. Shestakova; O. K. Vikulova; A. V. Zheleznyakova; M. A. Isakov; D. V. Sazonova; N. G. Mokrysheva (Сахарный диабет)
BACKGROUND. The clinical and epidemiological characteristics of diabetes mellitus (DM) and the quality of its therapy are the key prognostic dominant that determines the organizational aspects of the diabetic service. The continuous dynamic   monitoring of DM has been carried out in the Russian Federation (RF) since 1996 through the activities of the Federal Register of Diabetes Mellitus (FDR).AIMS. The aim of our study was to analyze the epidemiological characteristics of DM in the RF (prevalence, morbidity, mortality), the prevalence diabetic of complications, the state of carbohydrate metabolism (level of HbA1c) and the dynamics of the structure of glucose-lowering therapy (GLT) according to the FDR.MATERIALS AND METHODS. The database of FRD (https://www.diaregistry.ru/), 85 regions of the RF. The data are presented as of 01.01.2023 and in dynamics for the period 2010–2022.RESULTS. The total number of DM patients in the RF as of 01.01.2023 was 4 962 762 (3.31% of the population), including: Type 1 (T1) — 5.58% (277.1 ths), T2 — 92.33% (4.58 million), other DM types —2.08% (103 ths). The dynamics of prevalence over the 13-year period (2010→2022) was 146.0→191.0/100 ths people with T1, and 2036.2→3158.8/100 ths people with T2; morbidity in T1 12.3→8.2/100 ths population, in T2 260.1→191.4/100 ths population; мortality: T1 2.1→2.4/100 ths population, T2 41.2→86.1/100 ths of the population. The main cause of death was cardiovascular: in T1 38.6% cases, in T2 — 50.9%. Life expectancy (average age of death of patients): T1 was 52.7 years, the dynamics in males 50.9 → 50.7 years, females 62.1→56.0 years; in T2 — 74.2 years, males 69.5→70.4 years, females 74.2→76.1 years. The dynamic of DM duration from onset to the death: in T1 15.4→19.9 years; in T2 11→11.4 10.2→11.8 years. The proportion of patients with laboratory-measured HbA1c <7% in the dynamics of 2010–2022: with DM1 24.4%→29%, with DM2 41.5%→42.2%, with HbA1c ≥9.0%: with DM1 29, 4% → 20.4%, with DM2 13.8 → 9.0%.The incidence of diabetic complications as of 01.01.2023 in T1 and T2 patients: neuropathy 41.3% and 23.7%, nephropathy (CKD) 22.8% and 19.1%, retinopathy 28.9% and 12.3%, respectively. The structure GLT in T2 patients as of 01.01.2023: monotherapy — 41.6%; combination of 2 GLM — 30.0%, 3 GLM — 5.8%, insulin therapy in 18.3%.CONCLUSIONS. The information-analytical system FDR is a key tool for systematizing the most important epidemiological and clinical characteristics of DM based on data from real clinical practice, which allows optimizing the algorithm of patient management and improving the quality of care for diabetes.